2023
DOI: 10.3389/fonc.2023.1080720
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factors in tumors: Key regulators and therapeutic avenues

Abstract: Krüppel-like factors (KLFs) are a group of DNA-binding transcriptional regulators with multiple essential functions in various cellular processes, including proliferation, migration, inflammation, and angiogenesis. The aberrant expression of KLFs is often found in tumor tissues and is essential for tumor development. At the molecular level, KLFs regulate multiple signaling pathways and mediate crosstalk among them. Some KLFs may also be molecular switches for specific biological signals, driving their transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 225 publications
(251 reference statements)
0
9
0
Order By: Relevance
“…Adding to the epigenetic intricacy is the m6A RNA demethylase, FTO, which steers mRNA demethylation [ 32 ]. Such activity has been correlated with the destabilization of KLF3 mRNA, skewing cellular behavior towards osteosarcoma advancement and metastasis [ 33 ]. Recent studies suggest DNMT-1 inhibition can enhance the sensitivity of osteosarcoma cells to specific agents like cabozantinib.…”
Section: Resultsmentioning
confidence: 99%
“…Adding to the epigenetic intricacy is the m6A RNA demethylase, FTO, which steers mRNA demethylation [ 32 ]. Such activity has been correlated with the destabilization of KLF3 mRNA, skewing cellular behavior towards osteosarcoma advancement and metastasis [ 33 ]. Recent studies suggest DNMT-1 inhibition can enhance the sensitivity of osteosarcoma cells to specific agents like cabozantinib.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-24-2-5p downregulation was significantly correlated with the upregulation of MYC that remained upregulated also on day 14 after chronic exposure. Krüppel-like factors (KLFs) are a group of DNA-binding transcriptional regulators with essential functions in various cellular processes, including proliferation, migration, inflammation, and angiogenesis [65]. KLF expression is often altered in tumors, and this is essential for tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…KLF expression is often altered in tumors, and this is essential for tumor development. For instance, KLF8 is activated by transforming growth factor-β1 (TGF-β1) via SMAD2 and contributes to ovarian cancer progression [65,66]. Cherukunnath et al reported that the TGF-β1/SMAD2/KLF8 axis regulates epithelial-mesenchymal transition and contributes to ovarian cancer progression [66].…”
Section: Discussionmentioning
confidence: 99%
“…SEC61G participates in endoplasmic reticulum stress by interacting with CREB3 to promote the malignant progression of lung adenocarcinoma [ 38 ]. Krüppel-like factors (KLFs) are DNA-binding transcriptional regulators involved in various cellular processes, including proliferation, migration, inflammation, and angiogenesis [ 39 ]. KLF16 overexpression promoted lung cancer cell growth and invasion [ 40 ].…”
Section: Discussionmentioning
confidence: 99%